Random signal processing - Mix, Dwight F. 1932- (Prentice Hall, 1995)
Providing detailed coverage of Wiener filtering and Kalman filtering, this book presents a coherent treatment of estimation theory and an in-depth look at detection theory for communication and pattern recognition.